2001
DOI: 10.1055/s-2001-17925
|View full text |Cite
|
Sign up to set email alerts
|

Colon Tumors and Colonoscopy

Abstract: Sedation and PreparationBowel preparation is one of the main reasons for the low acceptance of colonoscopy. Up to 20 % of colonoscopies are repeated earlier than necessary, due to poor bowel preparation [1]. In a meta-analysis, 11 randomized controlled trials comparing sodium phospate (NaP) and polyethylene glycol (PEG) were pooled, including a total of 861 patients. NaP and PEG were rated as tolerable by 84.5 % and 67.6 % of the patients, and the quality of preparation was good in 82.3 % vs. 74.9 %. The autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Truly depressed lesions are rare (2.3 % in the Akita Red Cross Hospital series) but the rate of extension to the submucosa is as high as 31 %. This characterization received further confirmation from many Japanese series presented at the Digestive Diseases Week (DDW) 2001 in Atlanta [51]. It is concluded that the endoscopic detection of so-called ªflatº lesions should rather focus on depressed small lesions; this is why a highresolution endoscope is required.…”
Section: Relevance Of Endoscopic Staging Based On Morphologymentioning
confidence: 88%
See 1 more Smart Citation
“…Truly depressed lesions are rare (2.3 % in the Akita Red Cross Hospital series) but the rate of extension to the submucosa is as high as 31 %. This characterization received further confirmation from many Japanese series presented at the Digestive Diseases Week (DDW) 2001 in Atlanta [51]. It is concluded that the endoscopic detection of so-called ªflatº lesions should rather focus on depressed small lesions; this is why a highresolution endoscope is required.…”
Section: Relevance Of Endoscopic Staging Based On Morphologymentioning
confidence: 88%
“…The pattern in the vertical surface corresponds to the image seen by the pathologist by 7 % and 10 %, respectively. Incidence rates of colon cancer further declined between 1990 and 1996: by 2.7 % and 1.7 % per year in males and females, respectively [51].…”
Section: Detection In Inflammatory Bowel Diseasementioning
confidence: 99%